Perceived severity of diabetes and associated factors among patients attending a referral hospital in Port Harcourt, Nigeria - Onu, Roseline; Babatunde, Seye (International Journal of Research in Medical Sciences, 2018)
Background: Nigeria has recorded a rising profile of diabetes in recent times due to urbanization and transition to westernized lifestyles. Perceived severity, the extent to which people deem their ailment to be severe, is an attitudinal construct that partly explains how likely people would modify their health behaviours. The study aimed to determine the level and associated factors influencing perceived severity among type 2 diabetes patients in Port Harcourt, Nigeria. Methods: A cross-sectional study was conducted among 119 adults at the University of Port Harcourt Teaching Hospital. They responded to a structured interviewer-administered questionnaire that included a 7-item scale on perceived severity, and socio-demographic and medical-related characteristics. Results: The mean age was 56.84 ± 11.51 years; 42.0% were males and 58.0% females. Mean diabetes duration was 7.60±5.58 years and 48.7% reported hypertension as a co-morbidity. About half (56.3%) had low Perceived Severity Score (mean score<3) versus 43.7% with high Perceived Severity Score (c2=3.782, p=0.052). Sex, employment status, religion, duration of diabetes and presence of co-morbidity appeared to show an inverse relationship with perceived severity, however there was no valid association (p>0.05). Conclusions: This study revealed an equal prevalence of low and high perceived severity of diabetes. Findings suggested that an unemployed Christian female with over 5 years’ diabetes history and no co-existing illness was likely to have a low perceived severity. We recommend further studies to examine other attitudinal constructs, beyond perceived severity, for better understanding of beliefs underpinning the health behavior of diabetes patients in different settings.